Financial capability, coping strategy, and MSME resilience - Selfira Selfira; Adek Maulidya; Hidayah Yoanna Putri (Indonesia Auditing Research Journal, 2026)
The research investigates how financial capability contributes to the economic resilience of flood-affected MSME households, with coping strategies serving as an intervening mechanism in the relationship. Financial capability is conceptualized through four dimensions: financial knowledge, financial attitude, financial behavior, and financial skills. Using a quantitative survey framework, data were obtained from MSME households experiencing the impacts of flooding. The relationships among the study constructs were subsequently evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that each dimension of financial capability contributes to the development of coping strategies. Financial behavior exhibited the largest contribution, while financial knowledge, financial skills, and financial attitude showed comparatively smaller effects. Coping strategy significantly contributes to economic resilience, indicating its role as an adaptive mechanism in responding to economic shocks. Furthermore, flood impact has a substantial effect on economic resilience, highlighting the importance of disaster-related factors in shaping household economic outcomes. The findings support the Behavioral Finance perspective, suggesting that actual financial practices are more influential than financial knowledge alone in strengthening resilience. This research extends existing knowledge by positioning coping strategy as a mechanism linking financial capability and economic resilience among MSME households. The findings imply that policies aimed at improving MSME resilience should focus not only on financial assistance but also on strengthening financial capability and disaster-adaptive behavior.